MANAJEMEN STRATEGI DALAM PENINGKATAN MUTU MADRASAH - Atun Mardiah, Ai; Hadiyanto, Nahdi; Munawaroh , Nenden (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Improving the quality of education is a strategic challenge for madrasahs amid globalization and national education policy. Madrasahs are not only required to excel academically, but also to shape students’ character and spirituality. MA Darul Arqam Putri Garut, as a pesantren-based madrasah, seeks to integrate Islamic values with 21st-century competencies. However, obstacles remain in program implementation consistency, monitoring and evaluation systems, and the relevance of teacher training to classroom practices. This study aims to analyze the management of madrasah quality improvement strategies, including planning, implementation, monitoring, evaluation, and the role of leadership and institutional collaboration. The study employs a qualitative approach using a case study method through interviews, observations, and documentation. The findings indicate that quality improvement strategies have been systematically designed and supported by teacher training, academic supervision, and collaboration with LP2M Muhammadiyah. Nevertheless, effectiveness has not been optimal due to weak continuous monitoring and limited follow-up supervision. Strengthening data-based strategic management and continuous evaluation is essential to improve madrasah quality.